Assessment of fitness of foot‐and‐mouth disease virus A IND 27/2011 as candidate vaccine strain. Issue 5 (7th June 2021) - Beeragere Parameshwaraiah, Sreenivasa; Mohapatra, Jajati K.; Jumanal, Veena; Valia Valappil, Dhanesh; Subramaniam, Saravanan; Patel, Bhimnere Hanumanthagouda Manjunatha; Basagoudanavar, Suresh H.; Hosamani, Madhusudan; Pattnaik, Brahmadev; Singh, Raj Kumar; Sanyal, Aniket
Abstract: Antigenic profiling of recent field outbreak strains of foot‐and‐mouth disease virus (FMDV) serotype A in India has revealed considerable antigenic drift from the vaccine strain, A IND 40/2000, necessitating the selection of a new strain. The complete genome sequence of A IND 27/2011 was analysed. Vaccine quality attributes of the new candidate strain including potency as an inactivated vaccine in cattle were evaluated. The capsid coding region of A IND 27/2011 showed variation at eight antigenically critical amino acid positions from that of A IND 40/2000. The strain suited well with traits required by a vaccine in terms of its adaptability to adherent and suspension cell line, its immunogenicity, and potency as an inactivated vaccine formulation in cattle. Complete protection was observed upon homologous virus challenge at 4 weeks post‐vaccination. Taken together, these data demonstrate the suitability of A IND 27/2011 as an effective vaccine strain of FMDV serotype A.